Makna Warna Merah dan Putih dalam Video Klip Hingga Tua Bersama Rizky Febian - Fanthony Everell; Delliana, Santi (UNIVERSITAS KALBIS, 2024)
Color is a very sensitive thing that plays an important role for someone who sees it and has various meanings in it. Including the red and white colors in the video clip